Integrative description of a new species of Dugesia (Platyhelminthes, Tricladida, Dugesiidae) from southern China, with its complete mitogenome and a biogeographic evaluation - Ying Zhu; JiaJie Huang; Ronald Sluys; Yi Liu; Ting Sun; An-Tai Wang; Yu Zhang (Zoosystematics and Evolution, 2024)
A new species of freshwater flatworm of the genus Dugesia from Guangdong Province in China is described through an integrative approach, including molecular and morphological data, as well as mitochondrial genome analysis. The new species, Dugesia ancoraria Zhu & Wang, sp. nov., is characterised by: (a) a highly asymmetrical penis papilla, provided with a hunchback-like dorsal bump; (b) a short duct between seminal vesicle and ejaculatory duct; and (c) a postero-ventral course of the ejaculatory duct, which opens to the exterior at the subterminal, ventral part of the penis papilla. The molecular phylogenetic tree obtained from the concatenated dataset of four DNA markers (18S rDNA, ITS-1, 28S rDNA, COI) facilitated determination of the phylogenetic position of the new species, which shares a sister-group relationship with a small clade, comprising D. notogaea Sluys & Kawakatsu, 1998 from Australia and D. bengalensis Kawakatsu, 1983 from India. The circular mitogenome of the new species is 17,705 bp in length, including 12 protein coding genes, two ribosomal genes, and 22 transfer RNAs. Via analysis of gene order of mitochondrial genomes, the presently available pattern of mitochondrial gene rearrangement in the suborder Continenticola is discussed.